Prevalence and association of thyroid disorders with selected risk factors and severity of disease in patients confirmed of Coronary Artery Disease (Bangladesh Journal of Medical Science, 2020)
Objective: Subclinical hypothyroidism (SCH) has been identified as a risk for atherosclerosis and Coronary Artery Disease (CAD). The aim of this study was to determine the prevalence and association between hypothyroidism or subclinical hypothyroidism (SCH) and lipid parameters, anthropometric data and the severity of coronary artery disease (CAD) in patients awaiting Coronary Artery Bypass Graft Surgery (CABG) from a selected center.Method: A cross sectional analytical study was carried out amony patients awaiting CABG in a selected center. Thyroid profile (enzyme immunoassay method), lipoprotein (a) [Lp(a)], C- reactive protein (CRP) (immunoturbidimetric method) were determined and the Gensini score calculated. Lipid parameters and details of current medication were obtained from the medical records and anthropometric data were measured.Results: From a total of 102 patients 3% were on treatment for hypothyroidism and 15% had subclinical hypothyroidism. A significantly high (p= 0.04) percentage of SCH patients (75%) were dyslipidemic. There were no significant differences observed in lipid profiles and Lp(a) among SCH and euthyroid patients when the total sample or dyslipidemic sample was considered. However, a significantly high percentage (58%, p